Divorce reform and family mediation in England: an overview of the relevant provisions of the Family Law Act, 1996 - Ibrahim, Norliah; Abdul Hak, Nora (International Islamic University Malaysia, 2009)
The article focuses on the divorce reform in England. In 1996, the Family Law Act was passed by the Parliament in England, which is cited as Family Law Act, 1996. Unfortunately, after it was passed, there have been problems concerning its enforcement. Thus, the Government decided to postpone the enforcement of some parts of the Act. Generally, the suspension involves the law concerning the ground of divorce and mediation. However, it is felt that it is significant to deliberate on the Act although its position is still uncertain, as it has a lot of strengths and goodness in upholding the institution of family. Under the Act, mediation is introduced because is has many advantages such as it resolves disputes amicably and it can reduce backlog of cases in the court. It is hoped that the discussion in this article highlights the goodness of the divorce reform that took place in England to Malaysia. In Malaysia, the current Law Reform (Marriage and Divorce) Act 1976 has been enacted since 1976. Perhaps, we may learn from England in introducing a new piece of family law Act to the non-Muslims and to introduce mediation as an alternative means in resolving family disputes.